Gender Differences in the Provision of Job-Search Help. Issue 5 (October 2019) - Zhou, Min
The existing literature has well studied the use of social contacts in job search, including gender inequality, in using social contacts. What is missing is the perspective of social contacts who help others find jobs. Using a large data set from the 2012 China Labor-Force Dynamics Survey, this study reveals significant gender differences in the provision of job-search help. Compared with women, men are more likely to provide job-search help and especially show a greater likelihood of exerting direct influence on the hiring process. While women are gender neutral in their choice of help recipients, men display a selective preference for helping other men. This men's advantage of providing job-search help, especially influence-based help, and men's selective preference for helping other men, imply another prominent gender inequality in informal hiring in the labor market. This study suggests several theoretical propositions to explain the revealed gender differences in both "whether to help" and "whom to help, " providing a starting point for further research.